2015
DOI: 10.1155/2015/439820
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Complex Biogenic Silver Nanoparticle and Enoxaparin in Wound Healing

Abstract: The burns treatment is difficult, uncomfortable for the patient, and expensive for health system. Due to antimicrobial properties of silver nanoparticles (AgNP), these particles can avoid bacterial infection in wound and accelerate the wound healing. Furthermore, the complexation of AgNP with enoxaparin (low molecular weight heparin) may improve the healing process of lesions due to anti-inflammatory and angiogenic activity of enoxaparin (Enox). The aim of this study was evaluated the activity and toxicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…In addition, AgNPs treatment did not alter the urea and albumin concentrations, where they maintained normal levels upon treatment and after bacterial infection. On the other hand, Marcato et al reported a marked increase in the level of urea exerted by AgNPs, leading to less time required for wound healing (Marcato et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AgNPs treatment did not alter the urea and albumin concentrations, where they maintained normal levels upon treatment and after bacterial infection. On the other hand, Marcato et al reported a marked increase in the level of urea exerted by AgNPs, leading to less time required for wound healing (Marcato et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The major peaks in the FTIR spectrum of AgNPs (Fig. 3) were observed at 3777.15 cm À1 (medium NeH Stretching), 3170.26 cm À1 (medium bond, OeH stretching, carboxylic acids group), 2829.15 cm À1 (medium bond HeC] O; CeH stretching alkanes group), 2616.71 cm À1 (very strong bond, C]N stretching, nitriles group), 2123.19 cm À1 (weak bond, eC]Ce stretching, alkanes group), 1608.13 cm À1 (medium bond, NeH bending, amines group), 1517.95 cm À1 (strong bond, NeO assymmtric stretching, nitrocompounds group), 1408.86 cm À1 (medium bond, CeC stretching, aromatics group), 1331.24 cm À1 (strong bond, CeN stretching, aromatic amines group), 1112.59 cm À1 and 1031.25 cm À1 (medium bond, CeN stretching, aliphatic amines group), 895.86 cm À1 (strong NeH bending, amines group), 775.21 cm À1 (medium bond, CeCl stretching, alkyl halides group), 695.76 cm À1 (strong CeH bending, alkynes group), 606.77 cm À1 (medium bond, CeBr stretching, alkyl halides group) and 503.86 cm À1 (strong COO-stretching) respectively (Bhumi, Linga Rao, & Savithramma, 2015;Marcato et al, 2015;Metuku et al, 2014). The morphology and size of the synthesized AgNPs were determined by transmission electron microscopy (TEM) study.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests the potentiality of an S. aureus /MRSA‐specific protease in restricting PR‐39 translocation across the bacterial cell wall or in preventing binding specificity between the peptide and an internal target. Several studies have demonstrated strong negative correlations associating Ag nanoparticles and regional metalloproteinases, similar to those produced by S. aureus strains . Further, by natural reactivity and ROS production, Ag nanoparticles generate indentations across the bacterial membrane .…”
Section: Discussionmentioning
confidence: 99%